The First Molecular Identification of an Olive Collection Applying Standard Simple Sequence Repeats and Novel Expressed Sequence Tag Markers - Mousavi, Soraya; Mariotti, Roberto; Regni, Luca; Nasini, Luigi; Bufacchi, Marina; Pandolfi, Saverio; Baldoni, Luciana; Proietti, Primo (Frontiers in Plant Science, 2017)
Germplasm collections of tree crop species represent fundamental tools for conservation of diversity and key steps for its characterization and evaluation. For the olive tree, several collections were created all over the world, but only few of them have been fully characterized and molecularly identified. The olive collection of Perugia University (UNIPG), established in the years ’60, represents one of the first attempts to gather and safeguard olive diversity, keeping together cultivars from different countries. In the present study, a set of 370 olive trees previously uncharacterized was screened with ten standard SSRs and nine new EST-SSR markers, to correctly and thoroughly identify all genotypes, verify their representativeness of the entire cultivated olive variation, and validate the effectiveness of new markers in comparison to standard genotyping tools. The SSR analysis revealed the presence of 59 genotypes, corresponding to 72 well known cultivars, thirteen of them resulting exclusively present in this collection. The new EST-SSRs have shown values of diversity parameters quite similar to those of best standard SSRs. When compared to hundreds of Mediterranean cultivars, the UNIPG olive accessions were splitted into the three main populations (East, Center and West Mediterranean), confirming that the collection has a good representativeness of the entire olive variability. Furthermore, Bayesian analysis, performed on the 59 genotypes of the collection by the use of both sets of markers, have demonstrated their splitting into four clusters, with a well balanced membership obtained by EST respect to standard SSRs. The new OLEST (Olea expressed sequence tags) SSR markers resulted as effective as the best standard markers. The information obtained from this study represents a high valuable tool for ex situ conservation and management of olive genetic resources, useful to build a common database from worldwide olive cultivar collections, also based on recently developed markers.